Pengaruh Firm Size , Corporate Governance terhadap Manajemen Laba (Studi Kasus perusahaan Food and Beverages yang terdaftar di BEI Periode 2016-2018) - Farah Zairina; Ronny Malavia Mardani; M. Khoirul Anwarodin Broto S (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research aims to determine the influence, firm size, corporate governance of profit management partially. Population and samples in this research in the food and beverage sector companies were listed in IDX in 2016-2018 which amounted to 26 companies and which corresponds to the criteria of the criteria of 15 company known. The data retrieval technique uses the Purposive sampling method. The data retrieval technique with document data obtained from the company document is www.idx.co.id. Data analysis used SPSS version 20. The analysis tools used in this study are test normality, classical assumption test, double linear regression test and hypothesis test. Based on the results of this study concluded that the variable firm size of profit management does not affect the profit management and the corporate governance variables on the profit management negatively affect the negative and the impact on profit management. The company implements corporate governance strategy due to success or failure that can occur depending on the strategy. Shareholders, Board of Commissioners, Board of Directors, Risk Management Committee, audit committee, BOC members, board members, social responsibility, corporate ethics are some of the characteristics included in corporate governance, from research can be said that corporate governance of the company has a strong influence, corporate governance facilitates about the future company.Keywords: Firm size, corporate governance and profit management